2023
DOI: 10.32920/ryerson.14649540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fashion and Positive Psychology: Interactions Between Clothing, Mood, Self-Concept, and Well Being

Abstract: This qualitative positive psychology study investigated how women experience clothing and how those experiences interact with their emotions, mood, self-concept, and self-esteem, to understand how clothing can influence well-being. Seven women (ages 21-39) participated in a personal account questionnaire, daily clothing diary, and wardrobe interview. This research demonstrates how clothing can uplift mood, reinforce and validate self-concept, boost self-esteem, and enhance well-being. This research contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…By having friends as potential participants, this small sampling represents those who may share the same values and behaviours as myself. In a qualitative study conducted by JulianaScott (2018) she had a similar experience with gathering her friends for interviews. However, she found that for qualitative research it was beneficial to use convenience sampling as it provided rich data.…”
mentioning
confidence: 99%
“…By having friends as potential participants, this small sampling represents those who may share the same values and behaviours as myself. In a qualitative study conducted by JulianaScott (2018) she had a similar experience with gathering her friends for interviews. However, she found that for qualitative research it was beneficial to use convenience sampling as it provided rich data.…”
mentioning
confidence: 99%